Putting the First Amendment in Play: Name, Image, and Likeness Policies and Athlete Freedom of Speech - Ehrlich, Sam; Ternes, Neal (The Columbia Journal of Law & the Arts, 2021)
Following a unanimous defeat at the Supreme Court in National Collegiate Athletic Association (NCAA) v. Alston and facing an impending start date for various state laws that would force action on athletes’ ability to profit off their name, image, and likeness (NIL), the NCAA recently made the decision to simply allow states and member colleges and universities to promulgate NIL restrictions on their own. But while such a delegation helps the NCAA stave off relevant antitrust action against them, placing regulatory authority over college athlete endorsement and sponsorship deals in the hands of government actors like state legislators, governors, and public educational institutions brings constitutional analysis into play in a way that has not previously been seen in sports due to the wholly private natures of sports leagues and the NCAA. Along these lines, this Article applies First Amendment jurisprudence to three recurring NIL restrictions imposed by states and schools: (1) restrictions on athlete deals that conflict with institutional endorsement deals; (2) restrictions on athlete deals with vice industries like gambling and alcohol; and (3) broad restrictions on deals that conflict with undefined “institutional values.” To do so, we apply several First Amendment doctrinal frameworks—those concerning commercial speech, student speech, public employee speech, and the overbreadth doctrine—to provide a range of different means by which courts may interpret how the rights of college athletes are affected by NIL policies. In the end, we find that the nature of these restrictions as overbroad prior restraints of free speech creates significant doubt as to the constitutionality of many of these restrictions under the First Amendment. We conclude that such restrictions in no uncertain form “present a ‘realistic danger’ [that these actors] could significantly compromise recognized First Amendment protections,” including the advanced protections for political speech.